English-medium instruction from an English as a lingua franca perspective : exploring the higher education context - Murata, Kumiko, 1952- (Routledge research in language education, 2019)
"English is increasingly used as a lingua franca (ELF) in communicative situations the world over with the acceleration of globalisation. This is in line with the increased introduction of English-medium instruction (EMI) to higher education institutions in many parts of the world to further promote both students' and faculty's mobility to make them competitive and employable in the globalised world, and to make their institutions more attractive and reputable. EMI and ELF, however, are rarely explicitly investigated together despite the fact that the spread of EMI cannot be separated from that of ELF. This volume tackles the issue head on by focusing on EMI in higher education from an ELF perspective. The volume includes contributions by Asian, European, Middle Eastern, South American and Anglo-American scholars. It discusses language policies, attitudes and identities, analyses of classroom EMI practices, case studies and finally, pedagogical implications from an ELF perspective, incorporating also theoretical and empirical issues in conducting EMI courses/programmes. The volume will be of great interest and use, not only to those who are conducting research on ELF, EMI, CLIL, language policy and related fields, but also to classroom teachers and policy makers who are conducting and/or planning to start EMI courses/programmes in their institutions or countries all over the world"--